Histoid Leprosy - Rinasari, Umi; Sawitri, Sawitri; Listiawan, M. Yulianto; Prakoeswa, Cita Rosita; Agusni, Indropo; Santoso, Rachmat; Izumi, Shinzo (Institute of Topical Disease Universitas Airlangga, 2010)
Histoid Leprosy is a variant of lepromatous leprosy with characteristic clinical and histopathological features. Usually it is occured in lepromatous patients who relaps after dapsone monotherapy, in those with dapsone resistance , sometimes even after multidrug treatment, or at times, de novo with characteristic clinical and histopathological features. A 36 years old male, originated from Papua, visited to the skin outpatient clinic with translucent shiny nodules on the left elbow and thumb for the last 18 months. The nodules were multiple, painless and firm. There were nasal congestion, tickening of ear lobes and loss of eye brows. Patient did not have any history of previous antileprotic treatment. Routine blood examination was normal. Bacteriological examination of slit skin smear revealed acid-fast bacilli of Bacterial Index 4+ and Morfologic Index 10%. Histopathology of skin suggested lepromatous leprosy of histoid type with characteristic interlacing bundles of spindle shaped cells. Anti-PGL1 antibody (ELISA) revealed high titer of IgM (>5.300 u/ml) and also IgG anti PGL-1 (>5.300 u/ml). Polymerase chain reaction examination test to detect M.leprae was positive and direct sequencing of M.leprae isolate shows no mutation, which means no resistancy to MDT treatment. Treatment with MDTWHO regiment give clinical improvements and the histoid lesions disappered after 3 months treatment.The histoid form of leprosy in this case developed without any prior treatment of anti leprotic drugs ( de novo ). Some theoretical aspects of the patho-mechanism of histoid leprosy are discussed.